Correlation Between the Number of Drugs Prescribed and Potentially Inappropriate Medication (PIMS) Based on Beers Criteria in Geriatric Hypertension Outpatients at Dr. Soedomo Hospital in Trenggalek: Hubungan Jumlah Obat terhadap Potentially Inappropriate Medication (PIMS) Berdasarkan Beers Criteria pada Pasien Hipertensi Geriatri Rawat Jalan Rsud Dr. Soedomo Trenggalek - Widyaningrum, Esti Ambar; PDW, Kumala Sari; Astuti, Lelly Winduhani; Suhartatik, Sri; Rimawati, Rimawati; Sari, Eka Kartika (Universitas Tadulako, 2021)
Background: Geriatric patients are elderly people who have various diseases and or problems as a result of diminished organ, psychological, social, economic, and environmental functioning and who require integrated health treatments from a multidisciplinary team. Uncontrolled hypertension can lead to complications such as stroke, CHD, and kidney failure. The more incidence of complications, causing the geriatrics to get more drugs (polypharmacy). Polypharmacy is one of the risk factors for the occurrence of Potentially Inappropriate Medication (PIMs) that often occurs in geriatric patients. The 2019 Beers Criteria is one of the clear criteria that can be used to determine the prevalence of PIMs in geriatric individuals. Objectives: The objective of this study was to see if there was a correlation between the number of drugs administered to hypertensive geriatric outpatients at Dr. Soedomo General Hospital in Trenggalek and the incidence of PIMs. This study employed an observational study with an analytical approach and retrospective. This study included a sample of 85 prescriptions for outpatient geriatric hypertension outpatient at Dr. Soedomo General Hospital in the period October - December 2020 taken using the purposive sampling technique. Data were analyzed using the C contingency coefficient correlation test. Results: 67,1% of prescriptions contained â‰¥ 5 kinds of drugs and 32,9% of prescriptions contained < 5 kinds of drugs. Based on the incidence of PIMs, there were 97.6% of prescriptions for PIMs and 2.4% of prescriptions without PIMs. The C contingency coefficient correlation test shows the correlation coefficient (r) of 0.216 with a positive direction and p-value = 0.041. Conclusions: The number of drugs has a significant correlation and can cause the incidence of PIMs in geriatric patients with weak correlation strength. Collaboration between pharmacists and doctors is needed to provide the best therapy to patients, to maximize the role of pharmacists in monitoring drug use in geriatric patients at Dr. Soedomo Hospital in Trenggalek.